Exercise intensity during official soccer matches - Barbosa Coelho, D.; Coelho da Paixao, R.; Cruz de Oliveira, E.; Kappes Becker, L.; Batista Ferreira Junior, J.; Gomes Coelho, L.; Dias, J. C.; Silami-Garcia, E. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2016)
The aims of the study were: 1) to analyze the exercise intensity in several phases (six phases of 15 min) of soccer matches; 2) to compare the match time spent above anaerobic threshold (AT) between different age groups (U-17 and U-20); and 3) to compare the match time spent above AT between players` positions (backs, midfielders, forwards and wingabcks). Forty-four male soccer players were analyzed. To express players` effort, the heart rate (HR) was continuously monitored in 29 official matches. Further, HR corresponding to the intensity at the onset of blood lactate accumulation (OBLA) was obtained in a field test. The highest exercise intensity during match was observed in the 15-30 min period of the first half (p< 0.05). Match time spent above AT was not different between players from U-17 and U-20. In the comparison among players` positions, wingbacks showed lower time above AT (p< 0.05) than players of other positions. The intensity of effort is higher in the 15 to 30 minutes of play (intermediate phase), probably because the players are more rested in the beginning and wearing out is progressive throughout the game. It is also noteworthy that the intensity of exercise (HR and time above AT) of wingbacks was lower, probably because they usually are required to run a larger number of sprints and need more time below the AT to recover.